Effects of different dosages of caffeine administration on wrestling performance during a simulated tournament - Negaresh, R.; Del Coso, J.; Mokhtarzade, M.; Lima-Silva, A. E.; Baker, J. S.; Willems, M. E. T.; Talebvand, S.; Khodadoost, M.; Farhani, F. (European Journal of Sport Science, 2019)
The aim of the present study was to investigate the effects of different forms of caffeine administration on physical performance during a simulated wrestling tournament. In a double-blind and randomized experiment, twelve male freestyle wrestlers competed in a simulated wrestling tournament (5 wrestling matches consisting of 2 × 3-min wrestling rounds) following the ingestion of: a placebo, a high-dose of caffeine (10 mg/kg), a moderate-dose caffeine (4 mg/kg), a repeated-dose caffeine (2 mg/kg before each match to a total of 10 mg/kg) or a selective caffeine administration based on performance decrement previously measured (6.16 ± 1.58 mg/kg). The Pittsburgh Wrestling Performance Test (PWPT) was measured before each match to assess physical performance. In comparison to the placebo, the high dose of caffeine only reduced PWPT time before the first match (56.8 ± 2.0 vs. 52.9 ± 1.8 s; p < .05). The moderate dose of caffeine did not affect PWPT performance during the tournament. Both, the repeated dose and the selective administration of caffeine reduced PWPT time with respect to the placebo in the third (66.7 ± 1.8 vs. 63.1 ± 1.4 s; p < .05) and fourth matches (72.3 ± 2.4 vs. 65.9 ± 1.3 s; p < .05). However, only the selective dose of caffeine reduced PWPT time before the fifth match (62.7 ± 3.0 vs. 56.3 ± 2.0; p < .05). The dosage and administration of caffeine affect the ergogenic effects obtained following the ingestion of this substance. An individualized protocol to provide caffeine when physical performance is expected to be reduced might improve wrestling performance during the latter stages of a tournament.